Epidemiological characteristics of 778 patients who underwent surgical drainage of chronic subdural hematomas in Brasília, Brazil - Sousa, Emerson Brandão (2013)
Background: Chronic subdural hematomas (CSDHs) are common in neurosurgical practice. There are no publications that report large series of the epidemiological characteristics of this pathology in Brazil. The purpose is to describe a large series of surgical cases and analyze the epidemiological and clinical characteristics. Methods: We retrospectively analyzed patients with CSDH admitted into Neurosurgical Services at the Hospital de Base do Distrito Federal, Brasília, Brazil from 2006 to 2011. Age, sex, clinical feature, etiology, surgical procedure, side, clinical outcome, and recurrence were reviewed. Statistical tests were used to analyze data, and P < 0.05 was considered statistically significant. Results: The series included 778 patients. There were 643 (82.6%) male patients with a mean age of 64.3 ± 15.9 (range, 14–93) years. The principal symptom was headache (58.9%). The most frequent origin was a fall (282 cases, 36.2%), but the origin remained unclear in 281 (36.1%) patients. Mild head injury occurred in 540 (69.4%) cases. Burr holes with drainage were used as the surgical procedure in 96.5% patients, and 687 (88.3%) patients had a positive outcome. Mortality was 0%. Recurrence was observed in 42 cases. Conclusions: The occurrence of CSDHs is more common in elderly men. Treatment with burr holes and drainage is a simple and safe method for treatment. In our experience, CSDH presents decreased morbidity and mortality.